Ethnobiology Study on Nature and Processing Plants and Animals in Traditional Sea-Picking of Banyuwangi Regency - Sylvia Rimbanita Purwanto; Ika Lia Novenda; Erlia Narulita (Universitas Wiralodra, 2020)
The traditional sea-picking ceremony is a ritual carried out by the community as a form of gratitude for the abundance of sustenance provided by God, as well as for asking the safety of fishermen. Besides aiming for blessings and safety, the traditional sea picking ceremony also has an important role as a means of communication for fishermen and maintaining harmony among religious communities, therefore this traditional sea picking ceremony must be held once every year. The purpose of this study was to observe the nature and processing of plants and animals at sea picking ceremony and to find out the Use Value (UV) of plants, animals and the natural environment used. Sampling of informants was done by Purposive Sampling and Snowball Sampling; data obtained using semistructured interviews with open ended question types. The results showed there were 66 species from 37 plant families and 3 species from two animal families. While the Use Value (UV) analysis indicates that there were 12 plant species and one animal species that have a high Use Value (UV) which is 1, it shows that the species is most widely used in traditional sea picking ceremonies. Generally, it needs more efforts for further conservation.